Hukuman Cambuk di Aceh Nanggroe Darussalam: Tinjauan Yuridis atas Legitimasi Hukum dan Penyeimbangan Prinsip Hak Asasi Manusia - Herlina Aisyah; Deden Najmudin (Indo Publishing, 2026)
The implementation of caning punishment in the Aceh Qanun Jinayah is an implementation of Islamic law that obtains legal legitimacy through constitutional recognition of regional specificities. However, its existence and implementation practices still generate debate, particularly regarding its position within the national legal system and its conformity with human rights principles. This study aims to analyze the legal legitimacy of caning punishment within the framework of Indonesia's pluralistic national legal system and examine the dynamics of its implementation in response to human rights criticism. This study uses a normative legal method with a legislative and conceptual approach through a review of the 1945 Constitution, laws, the Qanun Jinayah, and legal literature. The results show that caning punishment has a valid and binding legal basis specifically in Aceh, and has undergone adjustments in its implementation, including through changes in the location of execution. The novelty of this study lies in the integrative analysis of the legal legitimacy and implementation practices of caning punishment. The contribution of this research is to enrich legal studies on the harmonization of Islamic law and human rights in the Indonesian rule of law.